2002
DOI: 10.1086/338758
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Screening of Fibroblast Growth-Factor Receptor 2 Reveals a Wide Spectrum of Mutations in Patients with Syndromic Craniosynostosis

Abstract: It has been known for several years that heterozygous mutations of three members of the fibroblast growth-factor-receptor family of signal-transduction molecules-namely, FGFR1, FGFR2, and FGFR3-contribute significantly to disorders of bone patterning and growth. FGFR3 mutations, which predominantly cause short-limbed bone dysplasia, occur in all three major regions (i.e., extracellular, transmembrane, and intracellular) of the protein. By contrast, most mutations described in FGFR2 localize to just two exons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
230
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(243 citation statements)
references
References 77 publications
7
230
0
6
Order By: Relevance
“…This situation is similar to two previous studies 15,21 in which mutations were detected in 18/20 and 25/28 Crouzon patients, respectively. In PS, we found 95% of mutations in our cohort of 20 patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This situation is similar to two previous studies 15,21 in which mutations were detected in 18/20 and 25/28 Crouzon patients, respectively. In PS, we found 95% of mutations in our cohort of 20 patients.…”
Section: Discussionsupporting
confidence: 92%
“…14 In 2002, novel mutations in other regions of the receptor including the IgII loop and the tyrosine kinase subdomains TK1 and TK2 have been reported. 15 Likewise, this study demonstrated that in a clinically homogeneous group of CS and PS patients, FGFR2 mutations were detectable in more than 90% of all cases, thus making the existence of an additional major locus very unlikely. 14 A recurrent mutation, A391E, in a third gene, FGFR3, accounts for a peculiar form of CS associating craniosynostosis with acanthosis nigricans also called crouzonodermoskeletal syndrome.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Most of the mutations are missense, or small in-frame insertions or deletions that affect the highly conserved extracellular FGFR ligand-binding domain. However, some recently described mutations involve the intracellular tyrosine kinase domain of FGFR2 and presumably function to activate downstream signaling pathways (Kan et al 2002).…”
Section: Fgf Receptor Mutations Induce Craniosynostosis Syndromesmentioning
confidence: 99%